Analisis kemampuan pemecahan masalah materi kecepatan dan debit berdasarkan teori john dewey pada peserta didik kelas 5 sekolah dasar - Rahma Natatama; Siti Kamsiyati; Anesa Surya (Universitas Sebelas Maret, 2023)
This aim of this research is to describe the ability to solve problems in speed and debit material based on John Dewey's theory on the 5th grade students of SD Djama'atul Ichwan Surakarta in the academic year 2019/2020. The method used in this research is descriptive qualitative with a phenomenological approach. The data source of this study was students of grade 5Bth at SD Djama'atul Ichwan, consisting of six children as research samples were taken by using a purposive sampling technique . The data collection technique was carried out by observation, interview, and document analysis with data validity testing using technique triangulation and time triangulation. Data were analyzed using the Miles and Huberman data analysis models. The results of this study indicate that students can determine the problem by meeting the two specified indicators. Students are quite able to formulate and evaluate problem-solving hypotheses because they only have one way as an alternative to problem-solving so that they only meet one indicator out of the two indicators set. Students are quite capable of applying the chosen problem-solving method because they have not been able to write problem-solving steps systematically so that they only meet three indicators out of the four indicators set. It can be concluded that the students did not succeed in meeting the indicators determining several alternative problem-solving and indicators of the problem-solving flow were written systematically. The result of this research provide insight into problem-solving abilities based on John Dewey’s theory and orm the basis of the further research. The result of this research also encourage teachers to determine effective strategies, models, and methods so they can improve students’ problem solving abilities.